Analysis of Production Factors on Agro Industry Production Value in Central Lombok Regency from an Sharia Economic Perspective - Baiq Sufia Kasih; Syawahid Syawahid; Nining Purwati (Universitas Muhammadiyah Makassar, 2025)
This study aims to analyze the function of production factors on the agro industry production value in Central Lombok Regency from an islamic economic perspective. It was hypothesized that an increase in production factors such as labor, capital, and raw materials would align with an increase in production value. The research employed a quantitative descriptive approach using secondary data from 2018-2022. The analysis included descriptive statistics, Compound Annual Growth Rate (CAGR), Pearson correlation, economic ratios, and productivity analysis. The results indicate a very strong correlation among production factors (r=0.944-0.999), with raw materials and production value showing the highest correlation (r=0.999). Labor productivity experienced an average decrease of 0.38% per year, while investment grew by 1.015% annually. The proportion of labor costs was only 4.72% of the production value, indicating a capital intensive characteristic. Raw material efficiency remained stable at 2.42, with value added reaching 58.66%. From an Islamic economic perspective, this industry demonstrates alignment with tawhid, but requires improvements in distributive justice ('adl) and maslahah optimization. This research contributes theoretically to the integration of Islamic economics with industrial analysis and offers practical recommendations for the development of a just and sustainable agro industry.